2021
DOI: 10.1101/2021.03.25.21254296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Simple, Home-Therapy Algorithm to Prevent Hospitalization for COVID-19 Patients:A Retrospective Observational Matched-Cohort Study

Abstract: Background. Effective simple, home-treatment algorithms implemented on the basis of a pathophysiologic and pharmacologic rationale to accelerate recovery and prevent hospitalization of patients with early coronavirus disease 2019 (COVID-19) would have major implications for patients and health care providers. Methods. This academic, matched-cohort study compared outcomes of 90 consecutive consenting patients with mild COVID-19 treated at home by their family physicians from October 2020 to January 2021 accord… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 37 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Suter and colleagues recently created an algorithm of the best and simplest home therapy for mild symptoms in early COVID‐19, to prevent hospitalization. 10 In their retrospective observational study, the control cohort (45 patients on 77; 58.44%) received paracetamol as home therapy, whereas in the cohort of patients following a recommended protocol only 6 of 86 (6.98%) used paracetamol as the leading therapy. The rate of hospitalization was 1.2% for patients undergoing the recommended protocol and 13.1% ( p = .007) for patients using predominantly paracetamol, that is, 44 cumulative days of hospitalization (recommended) versus 481 (controls).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Suter and colleagues recently created an algorithm of the best and simplest home therapy for mild symptoms in early COVID‐19, to prevent hospitalization. 10 In their retrospective observational study, the control cohort (45 patients on 77; 58.44%) received paracetamol as home therapy, whereas in the cohort of patients following a recommended protocol only 6 of 86 (6.98%) used paracetamol as the leading therapy. The rate of hospitalization was 1.2% for patients undergoing the recommended protocol and 13.1% ( p = .007) for patients using predominantly paracetamol, that is, 44 cumulative days of hospitalization (recommended) versus 481 (controls).…”
Section: Figurementioning
confidence: 99%
“…The rate of hospitalization was 1.2% for patients undergoing the recommended protocol and 13.1% ( p = .007) for patients using predominantly paracetamol, that is, 44 cumulative days of hospitalization (recommended) versus 481 (controls). 10 This evidence shows that using paracetamol at home to treat mild COVID‐19 symptoms, particularly in older adults with comorbidity, greatly enhanced the risk of hospitalization for dyspnea from interstitial pneumonia, so increasing the huge concern of crowding the intensive care units. Possible causes of this exacerbation might be the activation of prothrombotic mechanisms, currently reported as the leading pathogenetic cause of COVID‐19, alongside endothelial dysfunction.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently demonstrated that the implementation of an early home treatment protocol (based on cyclooxygenase-2 inhibitors, given early in the course of the disease at the very beginning of the onset of symptoms, even before the nasopharyngeal swab) almost eliminated the risk of hospitalization and related treatment costs. 7 The development of an effective adaptive immune response can limit the SARS-CoV-2 viral infection, but the uncontrolled activation of innate immune cells results in an aggressive hyperinflammatory response with the release of an excessive amount of pro-inflammatory cytokines in a process known as “cytokine storm”. 8 The cytokine storm leads to increased risk of vascular hyperpermeability, acute respiratory distress syndrome (ARDS), multiorgan failure, and eventually death when the high cytokine concentrations are unabated over time.…”
Section: Introductionmentioning
confidence: 99%